Design, Synthesis, and Docking Studies of New Torin2 Analogs as Potential ATR/mTOR Kinase Inhibitors - Althaf Shaik; Rashmi Bhakuni; Sivapriya Kirubakaran (Molecules, 2018)
Targeting DNA damage and response (DDR) pathway has become an attractive approach in cancer therapy. The key mediators involved in this pathway are ataxia telangiectasia-mutated kinase (ATM) and ataxia telangiectasia-mutated, Rad3-related kinase (ATR). These kinases induce cell cycle arrest in response to chemo- and radio-therapy and facilitate DNA repair via their major downstream targets. Targeting ATP-binding site of these kinases is currently under study. Torin2 is a second generation ATP competitive mTOR kinase inhibitor (EC50 = 250 pmol/L) with better pharmacokinetic profile. Torin2 also exhibits potent biochemical and cellular activity against ATM (EC50 = 28 nmol/L) and ATR (EC50 = 35 nmol/L) kinases. In this study, eight new Torin2 analogs were designed and synthesized through multistep synthesis. All the synthesized compounds were characterized by NMR and mass analysis. The newly synthesized analogs were evaluated for their anti-cancer activity via CellTiter-Glo® assay. Additionally, compounds 13 and 14 also showed significant inhibition for ATR and mTOR substrates, i.e., p-Chk1 Ser 317 and p70 S6K Thr 389, respectively. Compounds 13 and 14 displayed promising anti-cancer activity with HCT-116 cell lines in the preliminary study. Further, a comparative model of ATR kinase was generated using the SWISS-MODEL server and validated using PROCHECK, ProSA analysis. Synthesized compounds were docked into the ATP-binding site to understand the binding modes and for the rational design of new inhibitors.